Lineages of revolt : issues of contemporary capitalism in the Middle East - Hanieh, Adam (Chicago, ILL Haymarket Books, 2013)
​"Praise for Adam Hanieh's Capitalism and Class in the Gulf Arab States:"The first work to be published in English that gives a full understanding of the formation and development of the Gulf capitalist class."-CounterfireIn this illuminating and original work, Adam Hanieh demonstrates that the Arab Spring rebellions are about much more than democracy. Too often the Arab uprisings have been reduced to a simple expression of mass protest against authoritarian regimes. In an accessible and engaging style, Hanieh shows how an analysis of the specific nature of capitalist development in the Middle East is key to understanding these revolutions.Adam Hanieh teaches development studies at the School of Oriental and African Studies (SOAS). He is the author of Capitalism and Class in the Gulf Arab States. "-- Provided by publisher. "In this illuminating and original work, Adam Hanieh demonstrates that the Arab Spring rebellions are about much more than democracy. Too often the Arab uprisings have been reduced to a simple expression of mass protest against authoritarian regimes. In an accessible and engaging style, Hanieh shows how an analysis of the specific nature of capitalist development in the Middle East is key to understanding these revolutions"-- Provided by publisher.
Chapter 1: Theories and perspectives -- ​Chapter 2: Framing the region: imperialism and the Middle East -- ​Chapter 3: Mapping the Neoliberal experience -- ​Chapter 4: Capitalism and agrarian change in North Africa -- ​Chapter 5: Class and state in the West Bank: Neoliberalism under occupation -- ​Chapter 6: The regional scale: bringing the gulf Arab States back in -- ​Chapter 7: Crisis and revolution -- Appendixes -- Bibliographical -- Notes
​Includes bibliographical references (pages 219-265) and index.
Keywords: Economics; CAPITALISM; ECONOMIC CONDITIONS; POLITICAL ASPECTS; ECONOMIC ASPECTS; MIDDLE EAST